2022
DOI: 10.2147/cia.s350500
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of ‘Prediction of Adverse Drug Reactions in Older Inpatients (PADROI)’ Risk Assessment Tool

Abstract: Background Adverse drug reactions (ADR) detection and prediction methods in hospitalized older adults remain imprecise. The identification of the risk factors for ADRs in this group of patients is crucial to develop plausible prediction models. Objective This study aimed at developing and validating a “Prediction of ADR in Older Inpatients (PADROI)” risk assessment tool in hospitalized older adults. Methods and Materials We had previously con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Existing ADR predictive models are usually focused on hospitalized adults and the elderly. [11][12][13][14][15] Typically, the development of predictive clinical tools for ADR is based on collecting variables at the time of hospitalization. These variables are used to develop a score that identifies patients who, throughout their hospital stay, are at increased risk of ADR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing ADR predictive models are usually focused on hospitalized adults and the elderly. [11][12][13][14][15] Typically, the development of predictive clinical tools for ADR is based on collecting variables at the time of hospitalization. These variables are used to develop a score that identifies patients who, throughout their hospital stay, are at increased risk of ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Existing ADR predictive models are usually focused on hospitalized adults and the elderly 11–15 . Typically, the development of predictive clinical tools for ADR is based on collecting variables at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…99 Common tools for identifying PIMs include the Medication Appropriateness Index (MAI), HEDIS DAE, Beer's criteria, STOPP/ START criteria and EU-7-PIM list [Figure 3(c)]. [106][107][108][109] Wang et al 110 used Beer's criteria, STOPP/START criteria, and the EU-7-PIM list to evaluate the use of drugs in 560 elderly inpatients and found that Beer's criteria best predicted avoidable ADRs. However, for the elderly in Africa (Nigeria and South Africa), PIMs identified using Beer's criteria did not correlate to ADRs in hospitalized patients.…”
Section: Use Of Medication In Elderly Patientsmentioning
confidence: 99%
“…116 There are differences in pharmacotherapy in countries in different levels of development. For example, Yadesa et al 107 applied the Prediction of ADR in Old Patients (PADROI) model as a risk assessment tool for elderly inpatients (⩾60 years old) in low-income countries.…”
Section: Use Of Medication In Elderly Patientsmentioning
confidence: 99%